One Planet, One Health - Walton, Merrilyn (Sydney University Press, 2017)
One Planet, One Health provides a multidisciplinary reflection on the state ofour planet, human and animal health, as well as the critical effects of climate change on the environment and livelihoods of people. Climate change is already affecting many poor communities and traditional aid programs have achieved relatively small gains.Going beyond the narrow disciplinary lens and an exclusive focus on human health,a planetary health approach puts the ecosystem at the centre. With experience in eco-health methods, the contributors to One Planet, One Health postulate that the maintenance and restoration of ecosystem resilience should be a core priority, carried out in partnership with local communities.One Planet, One Health offers an integrated approach to improving the health of the planet and its inhabitants.